Rare earth Tb3+ doped LaFeO3 nanoparticles: New materials for high frequency devices fabrication. Issue 7 (August 2015) - Bashir, Bushra; Warsi, Muhammad Farooq; Khan, Muhammad Azhar; Akhtar, Muhammad Nadeem; Gilani, Zaheer Abbas; Shakir, Imran; Wadood, Abdul
Abstract: La1− x Tb x FeO3 nanoparticles (where x =0.00, 0.02, 0.04, 0.06, 0.08) prepared via micro emulsion method were characterized by Thermogravimetric analysis (TGA), X-ray diffraction (XRD), Scanning electron microscopy (SEM) and Fourier transform infra-red spectroscopy (FTIR). According to TGA analysis, the phase formation temperature identified was about 989 °C. Both XRD and FTIR confirmed the orthorhombic structure of La1− x Tb x FeO3 nanoparticles. The crystallite size estimated by XRD was in the range 40–75 nm. The cell volume measured by XRD was found to decrease upon substitution. The general trend deviated for x =0.08. The SEM analysis of nanoparticles estimated the particle size in the range 50–95 nm. After characterization the nanoparticles were subjected to the dielectric behavior evaluation in the frequency range 1×10 6  Hz to 3.0×10 9  Hz. Dielectric parameters were decreased by substitution of La 3+ with rare earth Tb 3+ ions. The dielectric studies showed the possible utilization of these nanomaterials in high frequency devices.